Absence Culture: The Effects of Union Membership Status and Union-Management Climate - Iverson, Roderick; Buttigieg, Donna; Maguire, Catherine (Relations industrielles / Industrial Relations, 2003)
SummaryDrawing from Nicholson and Johns (1985) typology of absence culture (N = 460 from 43 work groups), we found that greater similarity in union membership status between co-workers was associated with a lowering of a member’s absence culture, as was a more harmonious union-management (UM) climate. In addition, greater similarity in union membership was related to a lowered absence culture when the UM climate was perceived to be positive. The theoretical and practical implications of these findings for understanding the social context in which the absence culture of union members is engendered are discussed.